Caracterização de cicatrizes de deslizamentos por processamento de dados TM Landsat em Caraguatatuba - SP - Sestini, Marcelo Francisco; Florenzano, Teresa Gallotti (Geologia USP. Série Científica, 2004)
The objective of this work is to identify and to characterize landslide scars using TM Landsat 5 data. The study area is a sector of the Serra do Mar, in the Caraguatatuba municipality (São Paulo State, Brazil), which is favorable for these processes. Landsat TM composites were tested, as well as resultant images of the ratio bands and principal component transform, verifying the contribution of these processing to the landslide scars enhancement and feature distinction. These data were integrated to the digital elevation model. The results obtained are coherent with landslide areas and the literature.